Revision of the aperturally dentate Charopidae (Gastropoda: Stylommatophora) of southern Africa – genus Afrodonta s. lat., with description of five new genera, twelve new species and one new subspecies - Herbert, David (European Journal of Taxonomy, 2020)
The genus Afrodonta s. lat. is shown to comprise several lineages with distinctive shell characters primarily associated with the microsculpture of the protoconch and teleoconch, and the manner in which the apertural barriers are deposited. These lineages comprise Afrodonta s. str. and five new genera: Amatholedonta gen. nov., Biomphalodonta gen. nov., Costulodonta gen. nov., Iterodonta gen. nov. and Phialodonta gen. nov. Twelve new species are described, doubling the diversity of aperturally dentate charopid snails known from southern Africa. All new species are narrow-range endemics. A new subspecies of one of the more widely distributed species of Afrodonta s. str. is also described. Keys to genera and species are provided. New species and subspecies: Afrodonta geminodonta sp. nov., Af. inhluzaniensis leptolamellaris subsp. nov., Af. mystica sp. nov., Af. pentodon sp. nov., Amatholedonta fordycei gen. et sp. nov., Biomphalodonta forticostata gen. et sp. nov., Costulodonta bidens gen. et sp. nov., C. pluridens gen. et sp. nov., Iterodonta ammonita gen. et sp. nov., Phialodonta agulhasae gen. et sp. nov., P. atromontana gen. et sp. nov., P. aviana gen. et sp. nov. and P. rivalalea gen. et sp. nov. New synonyms: Afrodonta bilamellaris londonensis Solem, 1970 = Afrodonta bilamellaris Melvill & Ponsonby, 1908. New combinations: Afrodonta acinaces Connolly, 1933, Afrodonta burnupi Connolly, 1933 and Afrodonta trilamellaris Melvill & Ponsonby, 1908 are transferred to Costulodonta gen. nov.; Afrodonta bimunita Connolly, 1939 is transferred to Amatholedonta gen. nov.; Afrodonta introtuberculata Connolly, 1933 and Afrodonta perfida Burnup, 1912 are transferred to Phialodonta gen. nov.